A review of membrane fouling by proteins in ultrafiltration and microfiltration - Tanudjaja, Henry Jonathan (2023)
Fouling of ultrafiltration (UF) and microfiltration (MF) membranes by proteins is a major challenge in the bioprocessing and dairy industries, as well as in surface and wastewater treatment applications. This review attempts at presenting a comprehensive state-of-the-art understanding on protein fouling of membranes. Effects of operating conditions, along with properties of proteins and membranes, are discussed. Various tools and techniques used to characterize and monitor fouling are described. Different mitigation techniques and cleaning methods used are also presented. Two main factors have been identified as playing important roles in governing protein fouling, namely, ratio of protein size to membrane pore size and interfacial interactions (i.e., protein-protein and protein-membrane). Some directions for future research are suggested: (1) explore a wider range of proteins and their mixtures with respect to their fouling tendencies; and (2) create a comprehensive dataset that can be used to develop machine-learning models to enhance both predictive capabilities and mechanistic understanding.